a Pengertian Istilah Dan Makna Dalam Hukum: (Studi Analisis Term Syari’ah Dan Qanun) - Jauhari, Dwi Langgeng; Insan Labib, Muhammad Alfreda Daib (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
Shari'ah are the rules prescribed by Allah and the commands of His Prophet. Therefore, Shari'ah is a complete law that includes spiritual aspects related to God and social aspects related to the relationship between humans and the environment. Rigid and inflexible laws will create negative impacts and conflicts in society, so it is important to treat laws that are acceptable and adaptable to the environment. One of the ideas of modern Islamic law is qanun. The purpose of this study is to provide an understanding of shari'ah and qanun along with the taqnin of shari'ah, which is still a never-ending debate between groups that are against the existence of tannin Islamic law and groups that are against it. This research is library research. The type of research used in this paper is library research with a normative approach. The findings obtained from this research are; 1) shari'ah and qanun are different things but have interrelated relationships, 2) groups that support and do not support the existence of shari'ah tannin have their reasons.